The Role of Interpersonal Uncertainty in Prosocial Behavior - Anujit Chakraborty; Luca Henkel (CESifo GmbH, 2024)
In prosocial decisions, decision-makers are inherently uncertain about how their decisions impact others' utility – we call this interpersonal uncertainty. We show that people's response to interpersonal uncertainty shapes well-known patterns of prosocial behavior. First, using standard social allocation decisions, we replicate the classic patterns of ingroup favoritism, merit-based fairness ideals, and self-favoring behavior in dictator games. We then show that these patterns also arise in non-social decisions which have no consequences for others and instead solely reflect responses to interpersonal uncertainty. Behavior across social and non-social decisions is highly correlated, and self-reported interpersonal uncertainty predicts behavior in both situations. Moreover, exogenously varying interpersonal uncertainty shifts prosocial behavior in the direction that avoids such uncertainty. Our results quantify how beliefs in the form of inter-personal uncertainty influence prosocial behavior, which we estimate to be of similar importance to social preferences.
Keywords: C91; D01; D91; 330; prosocial behaviour; social preferences; ingroup versus outgroup decisions; dictator games; fairness preferences; interpersonal uncertainty